Correlation of changes in mean platelet volume with clinical stage of undifferentiated nasopharyngeal carcinoma - Raditya, I Gede Wahyu Adi; Suanda, I Ketut; Asthuta, Agus Rudi; Filbertine, Jessica (Oto Rhino Laryngologica Indonesiana, 2025)
Background: The mean platelet volume (MPV) is known to serve as a platelet activation assessment system for cancer prognosis evaluation. However, its role in nasopharyngeal carcinoma (NPC) has not been studied. Purpose: To determine the correlation between MPV changes and stage progression, in undifferentiated-type NPC. Method: A retrospective cross-sectional study was conducted in Ear, Nose, Throat-Head and Neck Surgery (ENT-HNS) clinic of Sanglah General Hospital, Denpasar, from May to June 2020. Patients with undifferentiated-type NPC meeting inclusion and exclusion criteria were included. The mean MPV values were determined by calculating the difference in MPV from complete blood count tests after six chemotherapy sessions, compared to before chemotherapy. Changes in NPC staging were assessed using TNM classification pre- and post-chemotherapy. Logistic regression analysis was performed to examine the correlation between MPV changes and clinical stage changes, considering the confounding factors. Result: A total of 30 subjects were participated in this study, with mean age of 50.70±12.55 years. A significant correlation was observed between MPV changes and changes in clinical stages T (p=0.021, r=0.419), N (p=0.025, r=0.408), and M (p=0.048, r=0.364). Linear regression analysis showed a significant correlation between MPV changes and clinical stage T (p<0.001, r=0.268), clinical stage N (p=0.042, r=0.039), and clinical stage M (p=0.003, r=0.059) after adjusting for age and sex as confounding factors. Conclusion: There was a significant correlation between changes in MPV and clinical stage progression (T, N, M), in patients with undifferentiated-type nasopharyngeal carcinoma